Clinical Correlation Between Overactive Bladder and Allergy in Children - Yin, Lu; Zhang, Zhou; Zheng, Yue; Hou, Ling; Zhao, Cheng-Guang; Wang, Xiu-Li; Jiang, Kai-Lei; Du, Yue (Frontiers in Pediatrics, 2022)
Background: The International Children's Continence Society defines overactive bladder (OAB) as a clinical syndrome characterized by urgency of urination usually accompanied by frequent urination and nocturia symptoms. This study aims to explore the correlation between overactive bladder (OAB) and allergy in children. Method: The clinical characteristics of 918 patients diagnosed with OAB from January 2020 to March 2021 were retrospectively analyzed. Risk factors for OAB were analyzed using logistic regression analysis, and the effect of desloratadine in the treatment of OAB was evaluated. Results: The incidence of allergic cough or allergic rhinitis in the mild OAB group was higher than the moderate–severe group. Urodynamics demonstrated that the proportion of patients with a sensitive bladder in the overactive detrusor group was significantly higher than the non-overactive detrusor group. The effective rate of treatment of OAB in patients complicated with allergies and taking desloratadine was 90.14%, which was significantly higher than in patients who were not taking desloratadine, and blood IgE level was a risk factor of ineffective treatment with desloratadine. Conclusion: OAB is correlated with allergies in children, and desloratadine can effectively improve OAB symptoms.